(1 − x)Bi0.5Na0.5TiO3–xBaTiO3 lead-free piezoelectric ceramics for energy-harvesting applications. Issue 7 (July 2015) - Kang, Woo-Seok; Koh, Jung-Hyuk
Abstract: Lead-free (1− x )Bi0.5 Na0.5 TiO3 – x BaTiO3 piezoelectric ceramics were investigated for energy-harvesting applications. In order to enhance the piezoelectric properties, the BaTiO3 content was varied at 0 ≤ x ≤ 0.1. Furthermore, the sintering temperature was optimized to enhance the piezoelectric properties and output energies. The piezoelectric charge coefficient was enhanced from 70 to 164 pC/N by introducing BaTiO3 and optimizing the sintering temperature to 1175 °C. The (1 − x )Bi0.5 Na0.5 TiO3 – x BaTiO3 lead-free piezoelectric ceramics exhibited a piezoelectric voltage coefficient of 47.03 × 10 −3 V m/N at x = 0.04, which is slightly higher than the piezoelectric voltage coefficient of lead-based piezoelectric ceramics. The generated output voltage and output power were 8.95 V and 18 nW, respectively, for 0.94Bi0.5 Na0.5 TiO3 –0.06BaTiO3 ceramics sintered at 1175 °C. The results suggest that lead-free (1 − x )Bi0.5 Na0.5 TiO3 – x BaTiO3 piezoelectric ceramics are good candidates for energy-harvesting applications.